Detail specification for radio frequency coaxial connectors (series SMA). 50 ohms, unsealed, soldered, centre contact, clamp outer for flexible cables, solder outer for semi-rigid cables. Full assessment level Part 1, (15th November 1985) - British Standards Institution,
No abstract available